Ascaris suum Nutrient Uptake and Metabolic Release, and Modulation of Host Intestinal Nutrient Transport by Excretory-Secretory and Cuticle Antigens In Vitro - Sarina Koehler (MDPI AG, 2021)
Ascaris suum, the most important pig parasite, also infects humans as a zoonotic pathogen. Malabsorption upon infection probably results from impaired nutrient transport, presumably mediated by the parasite’s excretory-secretory (ES) or cuticle somatic (CSO) antigens. The present study investigated the electrogenic transport (ΔIsc) of glucose, alanine and the dipeptide glycyl-l-glutamine (glygln), as well as glucose net flux rates in pig jejunal tissue after in vitro exposure to adult A. suum total ES or CSO antigens in Ussing chambers. ΔIsc of glucose, alanine and glucose net flux rate were significantly decreased after one hour of exposure to total ES antigen. In contrast, CSO antigens increased the transport of glygln. Additionally, nutrient uptake and ES antigen pattern were compared in culture medium from untreated adult worms and those with sealed mouth and anal openings. Untreated worms completely absorbed glucose, while cuticular absorption in sealed worms led to 90% reduction. Amino acid absorption was 30% less effective in sealed worms, and ammonia excretion decreased by 20%. Overall, the results show that A. suum total ES antigen rapidly impairs nutrient transport in vitro. Future studies confirming the results in vivo, narrowing down the ES components responsible and investigating underlying molecular mechanisms are needed.